التحليل التلوي: تعليم اللغة العربية بمساعدة الحاسب الآلي (CALL) كلغة أجنبية / لغة ثانية - Izza R.U., Nafisatul; Firmansyah, Haris Furkon Hasbi; Wafa, Ahmad Ainul; Ahsanuddin, Mohammad (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This study aims to analyze the meta-analysis of CALL in learning Arabic as a foreign/second language. Researchers use the meta-analysis method with literature review (Literature research). This research was conducted in several stages as follows: 1) Determining the topic of CALL in Arabic Language Learning. 2) Search and collect literature from various articles or journals. 3) Review and correct the information obtained. 4) Analyze and describe the data obtained. 5) Summing up the results of the study. Through a systematic literature search, this study presents results that describe CALL based on research objectives, research design, population, techniques and research data analysis. This research provides deeper insights related to Computer-Assisted Language Learning in learning Arabic as a foreign/second language.